Applying GIS to effectively map the usage of the UP SLIS Library - Belicario, Mark Anthony; Nario, Francis; Cabbab, Johann Frederick A. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2011)
Being able to effectively assess the usage of each space of a library will greatly improve the service of the library and can also help in attracting more users in that library.
In this study, the researchers tried to find out where users prefer to situate themselves within the library, their possessions and the activities that they do and also to create a system that will make these data to be understood easier. By knowing where most of the users stay, the staff of the library will have the knowledge of where it best to place some of the services that they offered and their materials as well.
In the duration of the study, the researchers were able to gather a total of 75 users of the library for a span of one week (May 18-23, 2011). The data gathered from here clearly shown that most users prefer to stay at Area B, which is the area near the air-condition and the reserve area of the library.
Recommendation in the study include having a more complex software in making the GIS to enable better handling and representation of data and also having a bigger library as tha area to have the study at.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Geographic information systems; Systems software